ASSOCIATION BETWEEN MATERNAL KNOWLEDGE OF THE LACTATIONAL AMENORRHEA METHOD AND STUNTING PREVENTION PRACTICES IN SIKUMANA INDONESIA - Maria Magdalena Mue Juwa; Sinta Inriani Olla (JTH: Journal of Technology and Health, 2026)
Stunting remains a major public health challenge in Indonesia, with maternal factors, including knowledge of postpartum family planning methods such as the Metode Amenore Laktasi (LAM), potentially influencing prevention practices. This study highlights LAM knowledge as an underexplored determinant of stunting prevention behavior. This study aimed to examine the association between maternal knowledge of LAM and stunting prevention practices in Sikumana, Indonesia. An analytical cross-sectional design was employed involving 60 mothers with children aged 0–24 months selected through simple random sampling. Data were collected using a structured questionnaire assessing socio-demographic characteristics, maternal knowledge of LAM, and stunting prevention practices. Data analysis included univariate and bivariate analysis using the chi-square test with a significance level of p < 0.05. The results showed that most mothers had moderate (41.7%) and poor (33.3%) knowledge of LAM, while only 25.0% had good knowledge. More than half of respondents (56.7%) demonstrated adequate stunting prevention practices. A statistically significant association was found between maternal knowledge of LAM and stunting prevention practices (p = 0.003), with mothers who had good knowledge more likely to exhibit adequate practices compared to those with lower knowledge levels. In conclusion, maternal knowledge of LAM is significantly associated with stunting prevention practices, highlighting the importance of strengthening maternal education as part of integrated strategies to prevent Stunting